2004
DOI: 10.1136/adc.2003.030924
|View full text |Cite
|
Sign up to set email alerts
|

Hospital accessibility and infant death risk

Abstract: This study of all 4889 infant deaths within the cohort of all 287 993 births in Cumbria, northwest England (1950-93), found no evidence of an increased risk of infant death with greater travel time to hospitals. R isk of mortality from asthma increases with distance from hospital. 1 In the developing world increasing distance from hospital has been shown to be a risk factor for perinatal mortality.2 With respect to the UK, Parker and colleagues 3 found no evidence of an increased risk of stillbirth in relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 5 publications
2
36
2
2
Order By: Relevance
“…This study is consistent with Combier et al (2013), Dummer and Parker (2004), and Moisi et al (2010) that travel time is not associated with neonatal mortality, while studies by Gryzbowski et al (2011), Okwaraji et al (2012, Ravelli et al (2011), andShoeps et al (2011) found a significant association with under-5 mortality and perinatal mortality (stillbirths and neonatal deaths). However, direct comparisons are not warranted for several reasons.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…This study is consistent with Combier et al (2013), Dummer and Parker (2004), and Moisi et al (2010) that travel time is not associated with neonatal mortality, while studies by Gryzbowski et al (2011), Okwaraji et al (2012, Ravelli et al (2011), andShoeps et al (2011) found a significant association with under-5 mortality and perinatal mortality (stillbirths and neonatal deaths). However, direct comparisons are not warranted for several reasons.…”
Section: Discussionsupporting
confidence: 77%
“…In such studies, pedestrian travel was the most common form of transport (Combier et al, 2013;Moisi et al, 2010;Okwaraji et al, 2012). The majority of studies consisted of a much larger sample size (Combier et al, 2013;Dummer & Parker, 2004;Grzybowski et al, 2011;Moisi et al, 2010;Okwaraji et al, 2012;Ravelli et al, 2011). Consistent with Combier et al (2013), and Grzybowski et al (2011), we excluded births less than 20 weeks gestation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations